The associations between women's empowerment measures, child growth and dietary diversity: Findings from an analysis of demographic and health surveys of seven countries in Eastern Africa - Joel J. Komakech; Christine N. Walters; Hasina Rakotomanana; Deana A. Hildebrand; Barbara J. Stoecker (Wiley, 2022)
Abstract Evidence on the efficacy of women's empowerment to improve child growth and minimum dietary diversity (MDD) in the Eastern Africa (EA) region is limited. This cross‐sectional study used recent Demographic and Health Survey data of mother-child dyads from seven countries in EA to examine the associations between women's empowerment measures, child growth and MDD. Length‐for‐age z‐scores, weight‐for‐length z‐scores and weight‐for‐age z‐scores were used to categorize growth indicators of 6-23 months old children. Multivariable logistic regression was used to identify significant associations. Among all countries, 32%-59% of children experienced growth failure. Children meeting MDD were 18%-45%. Women having self‐esteem were associated with lower odds of stunting (adjusted odds ratio [AOR] = 0.62 in Rwanda), wasting (AOR = 0.38 in Uganda), underweight (AORs = 0.60 and 0.57 in Tanzania and Uganda, respectively) and growth failure (AOR = 0.64 in Rwanda). Having health decision control in Burundi was associated with lower odds of stunting (AOR = 0.49) and child growth failure (AOR = 0.52) and higher odds of meeting MDD (AOR = 2.50). Having Legal empowerment among women increased the odds of stunting (AOR = 1.79 in Burundi), underweight (AOR = 1.77 in Uganda) and growth failure (AOR = 1.87 in Burundi). Economic empowerment showed mixed associations with child growth and MDD among some countries. Women's self‐esteem and health decision control were associated with better child growth and MDD for some countries in EA. Nutrition‐sensitive interventions aimed at improving child growth and MDD should consider local contexts when addressing women's empowerment.